Identifying the franchisee profiles franchisors prefer - Ramírez-Hurtado, José M.; Rondán-Cataluña, Francisco J.; Guerrero-Casas, Flor M.; Berbel-Pineda, Juan M. (Journal of Business Economics and Management, 2011)
This study identifies the franchisee profiles that franchisors prefer. Specifically, the goals of this study are: (1) to identify the characteristics that form the franchisee profile preferred by the franchisors operating in the Spanish market and (2) to contrast diverse hypotheses related to this profile. These hypotheses are related to the ideal franchisee, sector, financial level, number of franchisee units and age of franchisors. Criteria that franchisors look for in potential franchisees are ranked by importance. The value of the paper is significant as it provides a practical framework for franchisors for the selection process of franchisees when choosing from a group of potential franchisees. The franchisee profile was obtained using conjoint analysis, which is a decomposition methodology that is rarely used in this field.Article in English.Franšizė, jos naudotojai: Ispanijos atvejisSantrauka. Šio straipsnio autoriai, atlikę tyrimą, nustato, ko nori franšizės naudotojai, rinkdamiesi franšizę. Autorių atlikto tyrimo tikslai susiję – nustatyti savybes, būdingas franšizei (veikiančiai Ispanijos rinkoje), ir patvirtinti arba paneigti iškeltas hipotezes, susijusias su franšize. Šios hipotezės yra tiesiogiai susijusios su franšize, tam tikrais sektoriais, kuriuose jos dominuoja, taip pat finansiniu franšizės naudotojų lygiu, franšizės skaičiumi ir franšizės turėtojų amžiumi. Potencialių franšizės turėtojų kriterijai reitinguojami pagal svarbą.Reikšminiai žodžiai: kriterijus, franšizė, atranka, pirmenybė.